Knowledge transfer in preserving the Delanggu Rojolele local rice variety: a case study of becoming village designer in In-Herit course - Purwandaru, Pandu; Permanasari, Eka; Handoyo, Gani Cahyo; Pradana, Erik Wahyu (Gelar: Jurnal Seni Budaya, 2023)
Sabrang village was once known for its one-of-a-kind rice variety, Rojolele Delanggu. Despite this cultural abundance, the communities are currently abandoning these villages because they are deemed uneconomically viable. This paper investigates the ways in which knowledge-sharing initiatives involving local governments, women farming associations that have historically led farming rituals, and students from diverse developing countries contribute to the restoration of the Rojolele rice planting pattern. The project invited 20 international students from various developing countries to participate in the In-Herit 2022 program. The program was launched to increase student and local interest in becoming village designers through a case study of the preservation of local Rojolele Delanggu rice in Sabrang Village. This activity was broken down into three sections: (1) learning from locals, (2) participatory learning and action, and (3) proposing ideas to locals. The outcomes of this three-day project were a mapping of opportunities, challenges, and resolutions pertaining to the Rojolele Delanggu preservation initiative. The majority of students were able to quickly fit in with the locals, apply PLA materials, and were paired with student mentors who knew about farming community development activities in Delanggu farming regions.